Characteristics of Corticosteroid‐Resistant Secondary Immune Thrombocytopenia Associated With Connective Tissue Diseases in China: A Retrospective Comparative Study - Yangchun Chen; Yingying Shi; Yuechi Sun; Yun Peng; Guixiu Shi; Yuan Liu; Shiju Chen (Immunity, Inflammation and Disease, 2025)
ABSTRACT Objective Corticosteroid‐resistant secondary immune thrombocytopenia (ITP) is a challenging condition in clinical practice. This study aimed to explore the clinical and immunological characteristics of corticosteroid‐resistant secondary ITP associated with connective tissue diseases (CTD‐ITP). Methods We conducted a retrospective analysis of 201 CTD‐ITP hospitalized patients between 2014 and 2022. Patients were categorized as corticosteroid‐resistant or corticosteroid‐sensitive, and their demographic, clinical, and immunological data were compared. Logistic regression analysis was employed to identify independent predictors of corticosteroid resistance. Results Corticosteroid resistance was observed in 27.4% of patients. Compared with the corticosteroid‐sensitive group, the corticosteroid‐resistant group exhibited a higher percentage of CD3+ T cell (71.38% vs. 64.70%, p = 0.004) and CD3+CD8+ T cell (38.55% vs. 28.95%, p = 0.003), but a lower percentage of CD19+ B cell (13.70% vs. 22.45%, p = 0.001) in peripheral blood. No significant differences were found in other demographics, clinical features, or autoantibody profiles. The multivariable logistic regression analysis showed that higher percentage of CD3+CD8+ T cells (OR = 1.170, 95% CI: 1.014–1.350, p = 0.031) was an independent risk factor for corticosteroid resistance in CTD‐ITP patients. Conclusion This study revealed the potential role of higher CD3+CD8+ T cells in corticosteroid resistance among CTD‐ITP patients, and provided the potential biomarker for predicting corticosteroid therapy response.